Effect and Mechanism of Bifidobacterium animalis B94 in the Prevention and Treatment of Liver Injury in Rats - Zhang, Tianfang; Wang, Jie; Yao, Zhao; Ni, Lingmei; Zhao, Yifan; Wei, Shuang; Chen, Zuobing (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: To investigate the effect and mechanism of Bifidobacterium animalis B94 in the prevention and treat liver injury in rats. Methods: Specific pathogen-free (SPF) rats were selected as the healthy control group, liver injury group and B94 treatment group, with 6 rats in each group. After the model was established, the experimental animals were tested for serum liver function indicators, gut microbiota composition, intestinal metabolite composition, and histopathology. Results: Compared with those in the liver injury group, the white globulin ratio and serum globulin, alanine aminotransferase, aspartate aminotransferase, and indirect bilirubin levels in the B94 treatment group were significantly reduced. 16S rDNA analysis showed that the intestinal microbiota of the three groups of rats were significantly different. Metabolic profile analysis showed that there were significant differences in the intestinal metabolomes of the three groups. Haematoxylin–eosin staining of the intestinal mucosa and liver tissues showed that the degree of liver and intestinal tissue damage in the B94 treatment group was significantly lower than that in the liver injury group. Conclusion: Bifidobacterium animalis B94 can affect the process of liver injury in rats by improving liver function, reducing intestinal damage, and regulating the gut microbiota and metabolites production.